(NmEHANIKA (B:s (Nu^EBNIK (B/s - (NsTRELKOW(B, (NsERGEJ pAWLOWI^s ((NsANKT(B-(NpETERBURG (B;s (NmOSKWA (B;s (NkRASNODAR (B:s (NiZD(B-(NWO (B"(NlANX(B",s, 2005)
(NiZDANIE SODERVIT(B: (NKINEMATIKA TO^KI(B; (NOSNOWNYE ZAKONY DWIVENIQ (B- (NZAKONY DINAMIKI(B; (NKOLI^ESTWO DWIVENIQ SISTEMY TEL(B; (NRABOTA I \NERGIQ(B; (NSILY TRENIQ I DR(B.s
Keywords: (NfIZIKO(B-(NMATEMATI^ESKIE NAUKI (B- (NmEHANIKA (B- (Nu^EBNIK DLQ WYS[EJ [KOLYs